Channel Analysis and Marketing Margin of Instant Ginger Powder in Mpanau Village, Sigi Biromaru District, Sigi Regency - Endah Wahyunuing Asih (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
Dahlia Farmers Group has been engaged in the traditional instant powder drink industry, namely ginger. Of the various kinds of health drinks that this farmer group has produced, instant drink products are made from ginger, increasing sales every year. Currently, the Dahlia Farmers Group still has limitations in carrying out activities related to product marketing. This limitation impacts the lack of knowledge of producers regarding the marketing of instant red ginger powder. There are 3 (three) channels occur in the instant marketing of ginger powder in Mpanau Village, Sigi Biromaru District, Sigi Regency: Channel I: Producer Trader Consumer Retailer, Channel II: Consumer Online Producer, Channel III: Consumer Producer. Margin obtained from these three channels: First channel I: The margin earned in this channel is Rp.25,000,-/pack, Channel II: The margin obtained in this channel is Rp.15,000,-/pack. Channel III: Margin earned in this channel is Rp. 0,/pack. The Total Marketing Margin obtained in these three channels is Rp. 40,000.